2011
DOI: 10.1007/s00227-011-1772-x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of albacore tuna (Thunnus alalunga): population genetic structure in the North-East Atlantic Ocean and Mediterranean Sea

Abstract: Stock heterogeneity was investigated in albacore tuna (Thunnus alalunga, Bonnaterre 1788), a commercially important species in the North Atlantic Ocean and Mediterranean Sea. Twelve polymorphic microsatellite loci were examined in 581 albacore tuna from nine locations, four in the northeast Atlantic Ocean (NEA), three in the Mediterranean Sea (MED) and two in the southwestern Pacific Ocean (SWP). Maximum numbers of alleles per locus ranged from 9 to 38 (sample mean, 5.2-22.6 per locus; overall mean, 14.2 ± 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
5
28
0
1
Order By: Relevance
“…Moreover, our study suggests the existence of population structure within the Mediterranean Sea, which might reflect 2 genetically defined units: the western (the Balearic Sea sample) and the centraleastern (Tyrrhenian and Adriatic) population, which is consistent with Davies et al (2011). Although there are no pronounced oceanographic barriers which might limit gene flow among populations in the Mediterranean Sea, differentiation between Eastern and Western Mediterranean areas has also been reported for the congeneric bluefin tuna Thunnus thynnus (Carlsson et al 2004, Riccioni et al 2010) using mtDNA and/or microsatellite data.…”
Section: Genetic Diversity Between Populationssupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, our study suggests the existence of population structure within the Mediterranean Sea, which might reflect 2 genetically defined units: the western (the Balearic Sea sample) and the centraleastern (Tyrrhenian and Adriatic) population, which is consistent with Davies et al (2011). Although there are no pronounced oceanographic barriers which might limit gene flow among populations in the Mediterranean Sea, differentiation between Eastern and Western Mediterranean areas has also been reported for the congeneric bluefin tuna Thunnus thynnus (Carlsson et al 2004, Riccioni et al 2010) using mtDNA and/or microsatellite data.…”
Section: Genetic Diversity Between Populationssupporting
confidence: 86%
“…Indeed, in albacore, Takagi et al (2001) reported differentiation within and be tween the Pacific and Atlantic Oceans based on 4 micro satellite loci. Additionally, based on 12 micro sa tel lite loci, Davies et al (2011) described genetic differentiation within the Me diterranean Sea and between North Atlantic and South Pacific samples. Previous studies on the genetic structure of albacore populations used other types of markers, such as allozymes (Pujolar et al 2003), mtDNA (Chow & Ushiama 1995, Yeh et al 1997, Viñas et al 1999, Nakadate et al 2005, Wu et al 2009, and blood groups (Arriza balaga et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the differences in otolith post-core Sr : Ca and Ba : Ca and the timing of Sr : Ca cycles, albacore in the North Atlantic Ocean could be classified into two different migratory contingents: (1) a group captured within the Bay of Biscay, with early life movements between different water masses (starting at age-1þ); and (2) a group formed by individuals captured in offshore waters, with limited movements during the early life or annual migration starting at later stages. Davies et al (2011) described the potential presence of three different subpopulations within the eastern North Atlantic Ocean, which fits with our findings based on movement patterns. Furthermore, Bard (1981) reported that albacore captured in the Bay of Biscay (Cantabrian Sea) and offshore waters (Azores Islands) present different morphometric characteristics and hypothesised that different subpopulations may follow a different migration route in the eastern North Atlantic Ocean.…”
supporting
confidence: 90%
“…However, there has been no agreement about whether North Atlantic albacore exist as a single well-mixed stock or whether this group comprises several subpopulations or contingents. Population genetic structure investigations using microsatellite markers have revealed some insights into genetic heterogeneity with the potential presence of three subpopulations within the North Atlantic Ocean stock (Davies et al 2011), whereas single nucleotide polymorphisms did not detect significant heterogeneity (Albaina et al 2013;Montes et al 2012). Furthermore, there is some evidence to suggest that different groups with a different migration pattern may also exist within the North Atlantic Ocean (Bard 1981;Fonteneau 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Montes et al (2012) failed to find the stock structure differences between north and south Pacific albacore, as did Chow and Ushiama (1995). Microsatellite analysis of albacore tuna indicated also for the first time the potential presence of two separate populations in the Mediterranean Sea (Davies et al, 2011). More precisely, the Tyrrhenian and Adriatic Sea populations were differentiated from the Balearic Sea (Montes et al, 2012).…”
Section: Albacorementioning
confidence: 92%